Response of Arctic Ocean stratification to changing river runoff in a column model - Nummelin, Aleksi; Li, Camille; Smedsrud, Lars Henrik (Journal of Geophysical Research: Oceans, 2015)
A one-dimensional model of the atmosphere-ice-ocean column is used to study the effects of changing river runoff to the Arctic Ocean. River runoff is the largest contributor of freshwater to the Arctic and is expected to increase as the hydrological cycle accelerates due to global warming. The column model simulates the stratification of the Arctic Ocean reasonably well, capturing important features such as the fresh surface layer, the salty cold halocline, and the temperature maximum within the Atlantic Water layer. The model is run for 500 years with prescribed boundary conditions to reach steady state solutions. Increasing river runoff is found to strengthen the stratification and to produce a fresher and shallower surface mixed layer with warming (up to ∼1°C for a doubling of present-day runoff) in the Atlantic Water layer below. An important consequence is that the effect of the larger vertical temperature gradient is able to balance that of the stronger stratification and yield a close to constant vertical heat flux toward the surface. As a result, the sea ice response is small, showing only slight increase (up to ∼15 cm for a doubling of present-day runoff) in annual mean ice thickness. Limitations of the study include the idealized nature of the column model and uncertainties in the background vertical mixing within the Arctic Ocean. publishedVersion